Pengaruh Desentralisasi Fiskal Terhadap Pengentasan Kemiskinan Pada Provinsi Di Indonesia - Tony Putra; Sayifullah Sayifullah; Rizal Syaifudin (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
The purpose of this study was to determine the effect of regional original income, general allocation funds, special allocation funds, profit sharing funds, and local government spending on poverty alleviation in provinces in Indonesia. The research method uses quantitative methods. The research data source is secondary data in the form of panel data, namely provincial data in Indonesia for the period 2017-2021 obtained from the Indonesian Central Bureau of Statistics. Analysis of research data using panel data regression analysis. The results of the partial hypothesis test with the t test, it is known that the variables of local revenue, profit sharing and local government spending have a partially significant effect on poverty alleviation. Meanwhile, the general allocation fund and special allocation fund do not have a partial significant effect on poverty alleviation. The results of the F test show that regional original income, general allocation funds and special allocation funds, profit-sharing funds and local government spending have a significant simultaneous effect on poverty alleviation in provinces in Indonesia in 2017-2021.